2002
DOI: 10.1108/09513570210440586
|View full text |Cite
|
Sign up to set email alerts
|

Developments in content analysis: a transitivity index andDICTIONscores

Abstract: This paper responds to a call in the literature for methodological and empirical studies to advance research into accounting narratives, in the light of acknowledged areas of weakness and gaps in the accounting literature and with a view to investigating impression management. A general line of critique in the accounting literature points to a need to expand both the syntactic and thematic dimensions, with a particular focus on developing objective methods of analysis that allow computer‐based measurement. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 66 publications
2
139
0
13
Order By: Relevance
“…Prior studies have documented the presence of certain language characteristics (Smith and Taffler, 2000;Sydserff and Weetman, 2002) or the effective use of verbal tone and language bias (Aerts, 1994;Cho et al, 2010; in corporate narratives. In fact, Cho et al (2010) argue that "the more firm performance differs from a desired benchmark, the more management is motivated to manage impressions, and the more likely it is that narrative disclosure will be affected by a self-serving bias" (p. 432).…”
Section: Tone and Language Of Corporate Disclosurementioning
confidence: 99%
“…Prior studies have documented the presence of certain language characteristics (Smith and Taffler, 2000;Sydserff and Weetman, 2002) or the effective use of verbal tone and language bias (Aerts, 1994;Cho et al, 2010; in corporate narratives. In fact, Cho et al (2010) argue that "the more firm performance differs from a desired benchmark, the more management is motivated to manage impressions, and the more likely it is that narrative disclosure will be affected by a self-serving bias" (p. 432).…”
Section: Tone and Language Of Corporate Disclosurementioning
confidence: 99%
“…Prior research identifies that the writing style adopted by firms in the chairman's statement is contingent on FP. For instance, Sydserff and Weetman (2002) found that the narratives of firms experiencing poor FP are written in a style which detaches the reader from the message.…”
Section: Disclosure Theories Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The latter four methods are applied in this paper. Sydserff and Weetman (2002) is difficult to classify as it uses three methods: one reading ease manipulation and two rhetorical manipulation. 3 Ingram and Frazier (1980) is a corporate social reporting study.…”
Section: Vehicles For Impression Managementmentioning
confidence: 99%
“…To date, form-oriented content analysis studies investigating impression management have been relatively simplistic, for example, using word counts (Clatworthy and Jones, 2003), number of sentences (Kohut and Segars, 1992), coding of certain words (Sydserff and Weetman, 2002 …”
Section: Rhetorical Manipulation In Accounting Narrativesmentioning
confidence: 99%